Zmiany wartosci VO2max, AT i rAT (reversed AT) u mlodych zawodniczek gimnastyki artystycznej wywolane 12-tygodniowym treningiem - Suchanowski, A.; Baranska, K.; Kaczor, J. J.; Popinigis, J. (Medycyna sportowa, 2000)
Using cycloergometer "maximum work" test as a tool, the adaptive response of 11-13-years old girls (n = 5) to training of rhythmic gymnastics was evaluated. It is shown that as a result of 12 weeks of training (load: 6 days per week, 2-3 h per day) the VO2max increased from mean 31 ml/min/kg of body mass to 42 ml/min/kg body mass. However this increase was not accompanied by increase in total work output. AT increased only in 3 girls. In the same 3 girls after the period of training, the rAT time (time required to reach RQ = 1,0 during the recovery phase), was shorter (1,0 to 5 min). Samples of human m. obliquus abdominis internus were taken from 6 children, (boys 3-11-years old), and activity of 2 oxoglutarate dehydrogenase (OGDH, a marker indicating the amount of mitochondria in muscle) and cytosolic malate dehydrogenase (cMDH the enzyme involved in malate-aspartate shuttle) were measured. We did not find any correlation between activities of these two enzymes in muscles. This last finding suggests that in untrained children values of VO2max and AT can be not related each other.